Two FK506 resistance-conferring genes in Saccharomyces cerevisiae, TAT1 and TAT2, encode amino acid permeases mediating tyrosine and tryptophan uptake. - Schmidt, A (1994)
The macrocyclic lactone FK506 exerts immunosuppressive effects on T lymphocytes by interfering with signal transduction leading to T-cell activation and also inhibits the growth of eukaryotic microorganisms, including Saccharomyces cerevisiae. We reported previously that an FK506-sensitive target in S. cerevisiae is required for amino acid import and that overexpression of two new genes, TAT1 and TAT2 (formerly called TAP1 and TAP2), confers resistance to the drug. Here we report that TAT1 and TAT2 encode novel members of the yeast amino acid permease family composed of integral membrane proteins that share 30 to 40% identity. TAT1 is the tyrosine high-affinity transporter, which also mediates low-affinity or low-capacity uptake of tryptophan. TAT2 is the tryptophan high-affinity transporter. FK506 does not reduce the levels of TAT1 and TAT2 transcripts, indicating that the inhibition of amino acid transport by the drug is posttranscriptional.